2016
DOI: 10.1128/aac.02940-15
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in leuS Confers Reduced Susceptibility to GSK2251052 in a Clinical Isolate of Staphylococcus aureus

Abstract: c GSK2251052 is a broad-spectrum antibacterial inhibitor of leucyl tRNA-synthetase (LeuRS) that has been evaluated in phase II clinical trials. Here, we report the identification of a clinical isolate of Staphylococcus aureus that exhibits reduced susceptibility to GSK2251052 without prior exposure to the compound and demonstrate that this phenotype is attributable to a single amino acid polymorphism (P 329 ) within the editing domain of LeuRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Previous studies in the model organism Saccharomyces cerevisiae have suggested that resistance to tavaborole can evolve via mutations in the leuS gene (the gene that codes for leucyl-tRNA synthetase): these mutations occur in the editing domain of LeuRS and frequently impair the protein's editing activity (19,(37)(38)(39). A similar resistance mechanism was observed in clinical isolates of tavaborole-treated multidrug-resistant Escherichia coli (40) and in S. aureus that were treated with a tavaborole derivative, AN3365, the phase II clinical trials of which have been suspended due to the rapid development of AN3365 resistance (39). In the present study, therefore, we endeavored to determine if it is feasible to use this development of resistance, which likely arises at the expense of LeuRS editing, as a weakness via which tavaborole-resistant cells could be inhibited.…”
Section: Significancementioning
confidence: 99%
“…Previous studies in the model organism Saccharomyces cerevisiae have suggested that resistance to tavaborole can evolve via mutations in the leuS gene (the gene that codes for leucyl-tRNA synthetase): these mutations occur in the editing domain of LeuRS and frequently impair the protein's editing activity (19,(37)(38)(39). A similar resistance mechanism was observed in clinical isolates of tavaborole-treated multidrug-resistant Escherichia coli (40) and in S. aureus that were treated with a tavaborole derivative, AN3365, the phase II clinical trials of which have been suspended due to the rapid development of AN3365 resistance (39). In the present study, therefore, we endeavored to determine if it is feasible to use this development of resistance, which likely arises at the expense of LeuRS editing, as a weakness via which tavaborole-resistant cells could be inhibited.…”
Section: Significancementioning
confidence: 99%
“…[49][50][51] 16 can evade the main efflux mechanism and bring dawn to the clinical treatment of infections by multi-drug-resistant Gram-negative bacteria. 30 Unfortunately, due to the rapid development of AN3365 resistance, 53 16 has been discontinued in the phase II clinical trial. 54 However, in 2016, Monteferrante et al 55 found that the combination of 16 with colistin slowed the selection of resistant mutants.…”
Section: Inhibitors Targeting the Editing Site Of Leursmentioning
confidence: 99%
“…8 A boron-containing molecule 2 (AN3365, GSK2251052, Figure 1) 9 that inhibits leucyl tRNA-synthetase (LeuRS) by binding at the enzyme's editing site has also been evaluated clinically, although its development is encumbered due to the rapid emergence of resistance. 10,11 Nevertheless, to date, no catalytic site LeuRS inhibitor has been advanced to clinical investigation. Most of the precedent work to develop LeuRS catalytic site inhibitors has focused on non-hydrolyzable aminoacyl-AMP intermediate analogues such as LeuAMS 3 (Figure 1).…”
Section: Takedownmentioning
confidence: 99%